Edge-regular graphs with regular cliques. (June 2018) - Greaves, Gary R.W.; Koolen, Jack H.
Abstract: We exhibit infinitely many examples of edge-regular graphs that have regular cliques and that are not strongly regular. This answers a question of Neumaier from 1981.